55.4k views
1 vote
6x-4y=18 -x-6y=7 solve

1 Answer

4 votes

Answer:

Solution = (2, 1.5)

Explanation:

Step 1: Solve for y in 6x - 4y = 18

1. 6x - 4y = 18 → -4y = -6x + 18 → y = 1.5x - 4.5

Step 2: Substitute 1.5x - 4.5 for y in -x - 6y = 7

2. -x - 6(1.5x - 4.5) = 7

Step 3: Solve for x

3. -x - 9x + 27 = 7 → -10x + 27 = -20 → -10x = -20 → x = 2

Step 4: Substitute 2 for x in -x - 6y = 7

4. -(2) - 6y = 7

Step 5: Solve for y

5. -2 - 6y = 7 → -6y = 9 → y = -1.5

Hope this helps you out :)

User Heartcroft
by
5.1k points